Returns to education in West Germany: an empirical assessment - Charlotte Lauer; Viktor Steiner (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2000)
This paper analyses the developments in the returns to education in West Germany for the period from 1984 to 1997. Based on simple Mincer-type wage equations, we estimate a return of about 8% for men and 10% for women, and these returns have remained remarkably stable over the period. On the basis of more differentiated specifications of wage equations, we find evidence for the presence of cohort effects, in addition to time and lifecycle effects. Furthermore, the analysis shows that the choice of the sample of observation plays a crucial role. Indeed, huge differences exist between part-timers and full-timers, as well as between private and public sectors. Full-time working women have similar returns to schooling than men, and if female returns are declining and have become lower than male returns in the private sector, they are rather increasing and are higher than male ones in the public sector. Moreover, not all education degrees yield the same annual return. If one accounts for the different lengths of studies, the master craftsman degree yields the highest return. However, the estimates proved rather robust towards the specification of the wage equation and the estimation method.
Keywords: 330; Bildungsertrag; Schätzung; Geschlecht; Erwerbsverlauf; Arbeitszeit; Öffentlicher Dienst; Privatwirtschaft; Deutschland